Novel optineurin mutations in patients with familial and sporadic amyotrophic lateral sclerosis. Issue 11 (25th May 2011) - Del Bo, R; Tiloca, C; Pensato, V; Corrado, L; Ratti, A; Ticozzi, N; Corti, S; Castellotti, B; Mazzini, L; Sorarù, G; Cereda, C; D'Alfonso, S; et al.
Abstract : Background: Optineurin ( OPTN ), a causative gene of hereditary primary open-angle glaucoma, has been recently associated with amyotrophic lateral sclerosis (ALS) with mainly autosomal recessive, but also dominant, traits. To further define the contribution of OPTN gene in ALS, we performed a mutational screening in a large cohort of Italian patients. Methods: A group of 274 ALS patients, including 161 familial (FALS) and 113 sporadic (SALS) cases, were screened for OPTN mutations by direct sequencing of its coding sequence. All patients fulfilled the El Escorial criteria for probable or definite ALS and were negative for mutations in SOD1, ANG, TARDBP and FUS/TLS genes. Results: The genetic analysis revealed six novel variants in both FALS and SALS patients, all occurring in an heterozygous state. We identified three missense (c.844A→C p.T282P, c.941A→T p.Q314L, c.1670A→C p.K557T), one nonsense (c.67G→T p.G23X) and two intronic mutations (c.552+1delG, c.1401+4A→G). The intronic c.552+1delG variant determined a splicing defect as demonstrated by mRNA analysis. All mutations were absent in 280 Italian controls and over 6800 worldwide glaucoma patients and controls screened so far. The clinical phenotype of OPTN -mutated patients was heterogeneous for both age of onset and disease duration but characterised by lower-limb onset and prevalence of upper motor neuron signs. Conclusion: In this cohort, OPTN mutations were present both in FALS (2/161), accounting for 1.2% cases, and in SALS patients (4/113), thereby extending the spectrum of OPTN mutations associated with ALS. The study further supports the possible pathological role of optineurin protein in motor neuron disease.